2022
DOI: 10.3390/biology11070999
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Attenuates Muscle Impairment during Bed Rest through Muscle-Adipose Tissue Crosstalk

Abstract: The detrimental effect of physical inactivity on muscle characteristics are well known. Irisin, an exercise-induced myokine cleaved from membrane protein fibronectin type III domain-containing protein-5 (FNDC5), mediates at least partially the metabolic benefits of exercise. This study aimed to assess the interplay between prolonged inactivity, circulating irisin, muscle performance, muscle fibers characteristics, as well as the FNDC5 gene expression (FNDC5ge) in muscle and adipose tissue among healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Noteworthily, increased plasma levels have already been reported in humans after a 14-day episode of strict inactivity (bed-rest) [25]. These authors supported the idea that FNDC5/irisin is synthetized by adipose tissue rather than muscle.…”
Section: Fndc5/irisin Levels Are Increased In Smr Pupssupporting
confidence: 56%
“…Noteworthily, increased plasma levels have already been reported in humans after a 14-day episode of strict inactivity (bed-rest) [25]. These authors supported the idea that FNDC5/irisin is synthetized by adipose tissue rather than muscle.…”
Section: Fndc5/irisin Levels Are Increased In Smr Pupssupporting
confidence: 56%
“…According to D'Amuri et al, muscle-fat tissue crosstalk could represent a new biological target for the treatment of sarcopenia and muscle disuse atrophy [55]. Fourteen days of bed rest resulted in a loss of both mass and function in muscle but an increase in body fat tissue mass.…”
Section: Irisin and Its Role In Sarcopeniamentioning
confidence: 99%
“…The scientists concluded that there is a negative reverse connection relationship between muscle and adipose tissue. In particular, not only does muscle affect adipose tissue through irisin during exercise, but also adipose tissue protects muscle during the absence of physical activity [ 15].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
“…Особи, у яких виробляється більше ірізину характеризуються меншими втратами сили м'язів. Вчені дійшли висновку, що існує негативний зворотний зв'язок між м'язами та жировою тканиною, зокрема, не тільки м'язи впливають на жирову тканину через іризин під час тренування, але також жирова тканина захищає м'язи під час відсутності фізичної активності [15].…”
Section: основна частинаunclassified